Transformasi Kegiatan Rutin Madrasah Ibtidaiyah Sunan Ampel II Menuju Technology-based learning di Era Digital - husnah, Rif'atul; yaqin, Firdaus ainul (ELEMENTARY : Journal of Primary Education, 2023)
. Education in Madrasah Ibtidaiyah (MI), including in the Sunan Ampel II Maron madrasah ibtidaiyah institution, has undergone a significant transformation along with the development of the digital era. This research aims to investigate the transformation process of routine activities at MI Sunan Ampel II Maron towards technology-based learning with a comprehensive renewal approach. The main focus of this research is to analyze the implementation of technology in the context of Madrasah Ibtidaiyah (MI) learning, including aspects such as changes in teaching paradigms, learning methods, and curriculum development. The research methodology involves surveys, interviews and observations to gain an in-depth understanding of the transformation dynamics taking place. The application of technology is expected to not only increase learners' learning motivation but also advance their digital literacy. The research also explores the role of teachers and education staff in adapting to change, as well as efforts to improve their digital skills. These reforms are geared towards creating a learning environment that is responsive, creative and relevant to the demands of a digital society. The results of the study are expected to provide in-depth insights to education stakeholders, including governments, policy makers, teachers and parents, on the full potential and complexity of transforming the routine activities of Madrasah Ibtidaiyah. can be formulated that support the smooth implementation of technology-based learning in MI.